Pengembangan Konsep Tapak pada Masjid Jami’ Al Mujahidien Yosodadi, Kota Metro, Lampung: The Site Concept’s Development of Mosque Jami’ Al Mujahidien Yosodadi, Metro, Lampung Province - Kesuma, Yunita; Kurniawan, Panji; Basuki, Kelik Hendro (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The lack of planning on the development of the Mosque Al Mujahidien Yosodadi complex causes the undirected process of building so that the mosque layout and its supporting rooms are less synergistic, and the use of development funds becomes inefficient. Aiming to assist the mosque management team (takmir) in formulating the site concept of Mosque Al Mujahidien as the basis of its development stage, we conducted interviews, surveys, updating the existing conditions of the mosque building, site analysis, and identification of space requirements. The main result of the assistance is the formulation of ta’mir ideas to accommodate the relationship of multi dimensional activities (hablumminallah, hablumminannaas, and hablumminal ‘alam) to be adaptive with the development of commercial activities around. Therefore, the footprint can be a reference for the mosque management team in making a master plan and carrying out the stages of the physical development buildings is more visionary integrated. Finally, the expense of development funds becomes more efficient. Minimnya perencanaan pembangunan kompleks Masjid Al Mujahidien Yosodadi menyebabkan proses pembangunan yang tidak terarah sehingga layout masjid dan ruang-ruang penunjangnya kurang sinergis, dan penggunaan dana pembangunan menjadi tidak efisien. Bertujuan untuk membantu tim pengelola masjid (takmir) dalam merumuskan konsep tapak Masjid Al Mujahidien sebagai dasar tahap pengembangannya, kami melakukan wawancara, survey, pemutakhiran kondisi eksisting bangunan masjid, analisis lokasi, dan identifikasi persyaratan ruang. Hasil utama dari kegiatan ini adalah perumusan ide-ide ta’mir untuk mengakomodir relasi aktivitas multi dimensional (hablumminallah, hablumminannaas, dan hablumminal ‘alam) agar adaptif dengan perkembangan aktivitas komersial di sekitar. Oleh karena itu, tapak tersebut dapat menjadi acuan bagi tim pengelola masjid dalam membuat master plan dan melaksanakan tahapan pembangunan fisik bangunan yang lebih visioner terintegrasi. Akhirnya, pengeluaran dana pembangunan menjadi lebih efisien.